Chip Architectures: Multimodal Responses of Self‐Organized Circuitry in Electronically Phase Separated Materials (Adv. Electron. Mater. 9/2016). (14th September 2016) - Herklotz, Andreas; Guo, Hangwen; Wong, Anthony T.; Lee, Ho Nyung; Rack, Philip D.; Ward, Thomas Z.
Abstract : Confining an electronically phase‐separated film to the scale of its coexisting self‐organized metallic and insulating domains generates resistor‐capacitor circuit‐like behaviors, which delivers both electroresistive and mangetoresistive functionalities, as shown by A. Herklotz et al. in article number 1600189. These findings suggest that harnessing the mixed phases of strongly correlated single crystals may offer an important new avenue in crafting multifunctional chip architectures in next generation devices.